Implementation of Smart Corn Planter (SCP) to Support Food Security in Agricultural Area Gondosuli Village Probolinggo Regency - Iskandar Syah, Abdullah; Tri Handoko, Wahyu; Zainul Falah, Moh.; Kurniawan, Ryan; Hafid, Ahmad; Dwi Prasetya, Didik (CV. Creative Tugu Pena, 2023)
Gondosuli Village is located in Pakuniran, Probolinggo, East Java, and has an area of 11.66 km² (4.50 sq mi), consisting of agricultural land, settlements, public facilities, and mountain forests beneath Mount Rengganis. crops in Gondosuli village are dominated by rice and corn during the rainy season, and tobacco during the dry season. Corn has an important role as a commercial commodity in this village because it is used as animal feed, industrial raw materials, and also as a food ingredient. The process of planting seeds in Gondosuli village itself is still classified as using the traditional method where only using wood as a seed hole maker, and the seeds are inputted by human labor, and the distance between the seeds is only estimated by the farmer, in this way the seed planting process requires a lot of effort and time. big. A push corn planting tool or Smart corn planter is a tool used to grow corn efficiently and effectively on agricultural land. By using the Smart corn planter, farmers can grow corn quickly and more easily, and save effort and time. In addition, this tool can also help produce regular and even corn crops. Keywords: Smart Corn Planter (SCP), Gondosuli Village, Support Food Security